2013
DOI: 10.2196/mhealth.2641
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Delivering and Accessing Health Information Through Text Messaging Among Community Health Advisors

Abstract: BackgroundCommunication technologies can play a significant role in decreasing communication inequalities and cancer disparities by promoting cancer control and enhancing population and individual health. Studies have shown that technology, such as the mobile phone short message service (SMS) or text messaging, can be an effective health communication strategy that influences individuals’ health-related decisions, behaviors, and outcomes.ObjectiveThe purpose of this study was to explore usage of communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Characteristics of social media platform users communicating about HIV within our selected studies span a wide range of geographic locations, sexual orientations, ages, genders, races, and SES. This is encouraging, given the diverse and global nature of the HIV epidemic, and supports other studies that show the high acceptability and use of social media across diverse groups [ 25 , 38 , 74 ]. An assessment of the use of varying social media platforms by different types of users did not result in clear patterns; however, several studies in our review describe engagement of traditionally underserved populations, such as low-income individuals, MSM, and PLWHA on a variety of different social media platforms.…”
Section: Discussionsupporting
confidence: 84%
“…Characteristics of social media platform users communicating about HIV within our selected studies span a wide range of geographic locations, sexual orientations, ages, genders, races, and SES. This is encouraging, given the diverse and global nature of the HIV epidemic, and supports other studies that show the high acceptability and use of social media across diverse groups [ 25 , 38 , 74 ]. An assessment of the use of varying social media platforms by different types of users did not result in clear patterns; however, several studies in our review describe engagement of traditionally underserved populations, such as low-income individuals, MSM, and PLWHA on a variety of different social media platforms.…”
Section: Discussionsupporting
confidence: 84%
“…11,16,17 Other aspects of acceptability of mHealth solutions include improved logistics, decreased travel, and increased work speed. 9,11,15,16,[18][19][20][21][22] Finally, the literature highlights a socio-cultural aspect to acceptability with the use of mobile devices in health care delivery. Social respect, "confidence" and "empowerment" are identified as important aspects of acceptability, 11,[15][16][17]23 as are perceived improvement in job knowledge and capability enhancement -aspects of self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Social respect, "confidence" and "empowerment" are identified as important aspects of acceptability, 11,[15][16][17]23 as are perceived improvement in job knowledge and capability enhancement -aspects of self-efficacy. 11,13,20,22,24 Given the lack of consistency in measuring acceptability, the DI framework was utilized to guide the measures of acceptability for this study. Sekhon et al stress the importance of theorizing the construct of acceptability, 25 and in the case of acceptability for use in mHealth interventions, the DI framework was considered to be a useful theoretical model.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of SMS text messaging interventions in cancer prevention and control is growing in the general population and is emerging among minorities and the medically underserved, the number of studies that specifically focus on African Americans remain limited. In one study of predominately African American women, findings revealed that this group was receptive to receiving SMS text messages that focus on cancer and health information [54]. Similarly, some feasibility and positive acceptability of using SMS text messaging in a prostate cancer research project were also found for older African American men in the age range of 40 to 69 years [39].…”
Section: Introductionmentioning
confidence: 99%